Wavelength dependence of laser plasma interaction related to shock ignition approach. (16th November 2018) - Pisarczyk, T.; Gus'kov, S.Yu.; Dudzak, R.; Renner, O.; Batani, D.; Chodukowski, T.; Rusiniak, Z.; Dostal, J.; Demchenko, N.N.; Rosinski, M.; Parys, P.; Smid, M.; et al.
Abstract: This paper provides a summary of recent research connected with the shock ignition (SI) concept of the inertial confinement fusion which was carried out at PALS. In the experiments, Cu planar targets coated with a thin CH layer were used. Two-beam irradiation experiment was applied to investigate the effect of preliminary produced plasma to shock-wave generation. The 1ω or 3ω main beam with a high intensity >10 15 W/cm 2 generates shock wave, while the other 1ω beam with the intensity below 10 14 W/cm 2 creates CH pre-plasma simulating the pre-compressed plasma related to SI. Influence of laser wavelength on absorbed energy transfer to shock wave was studied by means of femtosecond interferometry and measuring the crater volume. To characterize the hot electron and ion emission, two-dimensional (2D) Kα -imaging of Cu plasma and grid collector measurements were used. In single 1ω beam experiments energy transport by fast electrons produced by resonant absorption made a significant contribution to shock-wave pressure. However, two-beam experiments with 1ω main beam show that the pre-plasma is strongly degrading the scalelength which leads to decreasing the fast electron energy contribution to shock pressure. In both the single 3ω beam experiments and the two-beam experiments with the 3ω main beam, do not show any clear influence of fast electron transport on shock-wave pressure. The non-monotonic behavior of the scalelength at changing the laser beam focal radius in both presence and absence of pre-plasma reflects the competition of plasma motion and electron heat conduction under the conditions of one-dimensional and 2D plasma expansion at large and small focal radii, respectively.